Implementation of Wordwall Quiz Media in Islamic Jurisprudence Learning to Increase the Activeness of Class X Students at MAN 1 Tuban - Himas Retna Kartika Putri; Aizatul Ulla; Erlina Nur Susanti; Atsarudin (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aimed to describe the implementation of the Wordwall Quiz media in Fiqh learning and to determine the improvement of student activeness among tenth-grade students at MAN 1 Tuban after the application of the media. The study employed a Classroom Action Research (CAR) method with qualitative and quantitative descriptive approaches conducted in two cycles, namely Cycle I and Cycle II. Qualitative data were collected through observation and documentation to describe the implementation process of Wordwall Quiz, while quantitative data were obtained through student activeness questionnaires. The results showed that the use of Wordwall Quiz created a more engaging, interactive, and enjoyable learning atmosphere, thereby increasing students' involvement in the learning process. The improvement in student activeness was evident in all indicators, including enjoyment, interest, enthusiasm, and participation. Overall, the percentage of student activeness increased from 73% in Cycle I to 87.2% in Cycle II, representing an increase of 14.2%. These findings indicate that Wordwall Quiz is an effective learning medium for enhancing the activeness of tenth-grade students in Fiqh learning at MAN 1 Tuban.